PENGARUH MOTIVASI BERIBADAH DITENGAH COVID-19 TERHADAP SIKAP KEBERAGAMAAN - Nur Irsyadiah; Syahrullah; Alviah Purwaningsih (Fakultas Agama Islam Universitas Islam Jakarta, 2022)
This research is motivated by the author's sensitivity in seeing the current phenomenon, namely the Covid-19 pandemic that affects almost all aspects of life. One aspect that gets quite a big influence is the aspect of worship. Worship activities and attitudes towards community religious issues must undergo new adaptations that must conform to the health protocols set by the government. Seeing this phenomenon, the author is interested in examining how the influence of worship motivation in the midst of the Covid-19 pandemic on religious attitudes between communities. The purpose of this study was to find out how the influence of motivation to worship in the midst of the Covid-19 pandemic on people's religious attitudes and to find out how much influence it had. This research was conducted from August to December 2020 in Cakung District. The method used is descriptive correlational analysis with data analysis using Product Moment. This type of research is field research using a quantitative approach. For data collection using a questionnaire on a questionnaire instrument. Based on the data that the authors obtained, the authors obtained very good results. From the results of calculations through the r test formula with ro results of 0.938, then these results are greater than rt with a significant level of 5%, namely 0.279 and 1%, namely 0.361. It can be concluded that the influence of worship motivation on the attitude of community diversity is very high, which is 94%.